2015
DOI: 10.1021/acs.chemmater.5b02918
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Performance Degradation of Fe-Based Layered Oxides in Sodium-Ion Batteries: Instability of Fe3+/Fe4+ Redox in α-NaFeO2

Abstract: The emergence of sodium-ion batteries (SIBs) employing cathodes based on earth abundant sodium and iron is expected to be ideal for large-scale electrical energy storage systems, for which the cost factor is of primary importance. However, these iron-based layered oxides still show unsatisfactory cycle performance, and the redox of the fleeting Fe3+/Fe4+ couple needs to be better understood. In this study, we examine the quasi-reversibility of the layered α-NaFeO2 cathode in sodium-ion cells. A NaFeO2 powder s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
171
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(180 citation statements)
references
References 27 publications
9
171
0
Order By: Relevance
“…[91] Recent work Reproduced with permission. [45] Copyright 2015, American Chemical Society. c) Synergy between electrochemistry and in situ XRD through sodium-ion intercalation in P2-Na x CoO 2 .…”
Section: Mostly Studied Single-metal-based Oxidesmentioning
confidence: 99%
“…[91] Recent work Reproduced with permission. [45] Copyright 2015, American Chemical Society. c) Synergy between electrochemistry and in situ XRD through sodium-ion intercalation in P2-Na x CoO 2 .…”
Section: Mostly Studied Single-metal-based Oxidesmentioning
confidence: 99%
“…The decomposition process can be initiated by many factors, such as moisture, elevated temperature, and strongly oxidizing environments. For example, Lee et al [19] reported that in a charged state of α-NaFeO 2 , more than 20% of the formed Fe 4+ species would spontaneously react with electrolyte during open-circuit storage due to its strong oxidization capability (Figure 2a). This oxidation slabs upon exposure to high voltages because of its anomalously large interlayer distances (7.0 Å), which could significantly deteriorate the sodium storage reversibility.…”
Section: Issues Related To High-voltage Electrochemical Operationmentioning
confidence: 99%
“…Reproduced with permission. [19] Copyright 2015, American Chemical Society. b) Calculated interlayer distance variation versus sodium content in Na x Ni 0.22 Co 0.11 Mn 0.66 O 2 electrodes.…”
Section: Issues Related To High-voltage Electrochemical Operationmentioning
confidence: 99%
“…When applying a higher charging voltage above 3.5 V, the irreversible structural degradation caused by Jahn-Teller distortion and polarization results in a significantly deteriorated rate reversibility and a big loss of sodium transition pathway. [54] Nonetheless, a-NaFeO 2 can present a high thermal stability which is a concern more in largescale application such as EVs to avoid serious security issues. The fully charged Na 0.58 FeO 2 powder decomposed thermally at a temperature higher than 300 °C, showing a better thermal stability in the electrolyte than its counterparts in LIBs.…”
Section: Single Transition-metal Oxidesmentioning
confidence: 99%